Do Oil Rents Deter Foreign Direct Investment? The Case of Saudi Arabia - Haque, Mohammad Imdadul (International Journal of Energy Economics and Policy, 2020)
The relationship between foreign direct investments (FDI) and natural resource endowment of a country is contentious. This study attempts to study this relationship for Saudi Arabia that is primarily an oil-producing country. In the process, it would also assess the role of institutions, trade openness, and domestic investments in attracting FDI. Using the methodology of cointegration over the data for the period 1984-2016, the study ascertains the presence of ‘resource curse' in terms of attracting FDI. The study discovers new findings as to the resource curse in attracting FDI are not because of institutional quality which has a positive relationship with FDI. The results also indicate the absence of crowding out of domestic investments. Finally, the study recommends channeling FDI to Greenfield projects with the maximum transfer of management and technology. Keywords: Natural Resource, Institutions, Trade openness, Crowding-out, Cointegration JEL Classifications: E02; F21; O43; P33 DOI: https://doi.org/10.32479/ijeep.10359